Modernism and the theatre of the baroque - Armond, Kate (Edinburgh critical studies in modernism, drama and performance., 2018)
Modernism and the Theatre of the Baroque fashions an independent aesthetic for modernist writers and texts that challenges many high modernist qualities promoted by James Joyce and T.S. Eliot.